Curcumin-Induced Membrane Property Changes in DMPC Multilamellar Vesicles and the Effects of Membrane-Destabilizing Molecules on Curcumin-Loaded Multilamellar Vesicles - Sahu, Anand Kumar (Langmuir : the ACS journal of surfaces and colloids, 2021)
Curcumin (CUR) is the major bioactive component of turmeric (Curcuma longa), commonly used as a spice and traditional medicine in India. CUR possesses a wide range of pharmacological benefits, including antioxidant, anticarcinogenic, antimutagenic, anti-inflammatory, anti-Alzheimer, and anti-Parkinson effects. The CUR-membrane interaction is believed to be the reason for such biological activity of CUR. Several research groups have modeled the interaction of CUR with artificial model lipid membranes using various techniques such as nuclear magnetic resonance (NMR), small-angle X-ray scattering (SAXS), and differential scanning calorimetry (DSC). However, the mechanism of its action is still unclear. A fluorescent-probe-based technique could be advantageous to study the CUR-lipid membrane interaction due to its sensitivity toward the local environment and its multiparametric nature. In this work, we have used the intrinsic fluorescence properties of CUR to investigate CUR-induced physical property changes in 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) multilamellar vesicles (MLVs) at various CUR concentrations. By rationalizing the results of steady-state fluorescence intensity, fluorescence anisotropy, temperature-dependent fluorescence intensity, temperature-dependent fluorescence anisotropy, and quenching experiments, we have proposed a model showing concentration-dependent effects of CUR on the DMPC bilayer membrane. We suggest that at low concentrations (≤1 mol %), CUR is homogeneously distributed in the DMPC bilayer membrane in both the solid gel (SG) and liquid crystalline (LC) phases. At high concentrations (>1 mol %), CUR molecules form segregated domains that fluidize both membrane phases. However, the CUR-induced fluidization is less pronounced in the LC phase as some CUR molecules from the domain partition into the bilayer core. Further, the effects of membrane-destabilizing molecules such as bile salts, capsaicin (CAP), and piperine (PIP) on CUR-loaded DMPC multilamellar vesicles were studied. Our work also shows that CUR has a stabilizing effect on the DMPC membrane at high concentrations